Pengaruh Struktur Modal, Ukuran Perusahaan, dan Likuiditas Terhadap Profitabilitas Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia - Julfadli Alhami; Tuti Meutia; Nurliza Lubis (Ali Institute of Research and Publication, 2026)
This study aims to analyze the influence of capital structure, firm size, and liquidity on the profitability of technology sector companies listed on the Indonesia Stock Exchange (IDX). Profitability is measured using Return on Assets (ROA), capital structure via the Debt to Equity Ratio (DER), firm size via the natural logarithm (Ln) of total assets, and liquidity via the Current Ratio (CR). This study employs a quantitative research approach using secondary data. The population consists of 46 technology sector companies listed on the IDX. The sample was selected using a purposive sampling technique, resulting in 48 observations derived from 8 technology companies listed on the IDX over the 2019–2024 period. The analysis methods used include multiple linear regression and classical assumption testing, comprising the t-test, F-test, and coefficient of determination test. The results indicate that, individually (partially), capital structure and liquidity have a positive and significant effect on profitability, whereas firm size does not have a significant effect. Simultaneously, the three variables significantly influence profitability, with a significance value of 0.000. The coefficient of determination shows that 99.3% of the variation in profitability can be explained by the research model. The study's implications highlight the importance of managing capital structure and liquidity to enhance the profitability of technology sector companies. Keywords: Capital Structure, Firm Size, Liquidity, Profitability